Postmarketing analysis of aflibercept-related sterile intraocular inflammation - Hahn, Paul; Chung, Mina M; Flynn, Jr, Harry W; Huang, Suber S; Kim, Judy E; Mahmoud, Tamer H; Sadda, SriniVas R; Dugel, Pravin U (JAMA ophthalmology, 2015)
Aflibercept-related sterile inflammation, an event that is poorly understood, has been the subject of ongoing postmarketing reports. To analyze cases of aflibercept-related sterile inflammation reported to the American Society of Retina Specialists (ASRS) Therapeutic Surveillance Committee (TSC), an independent task force formed to monitor drug- and device-related safety events. A retrospective review of 56 cases in 55 patients was performed of all cases of sterile inflammation after aflibercept injection that were voluntarily reported by 12 practices throughout the United States to the ASRS TSC from December 1, 2011, through February 12, 2014. Cases of aflibercept-related sterile inflammation were analyzed for baseline and demographic information, presenting symptoms and findings, visual acuity changes, injection technique, and management details. Among 56 reported cases of sterile inflammation, mean time to onset was 3.5 days (median, 2 days; range, 0-30 days). Most cases consisted of initial loss of vision and intraocular inflammation without prominent redness, severe pain, or hypopyon. Thirty-seven cases (66%) were treated with topical corticosteroids and/or observation alone. Mean time to resolution was 28.6 days (median, 28 days; range, 4-84 days). Although final vision was overall unchanged, some patients developed permanent vision loss, which may have resulted from inflammation and/or progression of the underlying disease. Age older than 80 years was associated with worse visual outcomes. No difference in visual outcome was detected in patients with sterile inflammation undergoing topical therapy alone vs invasive procedures (vitreous biopsy and/or intravitreal antibiotic administration and/or vitrectomy). With the largest number of reported cases of aflibercept-related sterile inflammation to our knowledge, this analysis suggests typical findings and an often favorable prognosis of this event. Analysis of real-world, postmarketing data has limitations, and these findings should be considered as hypothesis-generating assessments rather than a definitive reflection of this event or its typical course. Distinguishing sterile inflammation and infectious endophthalmitis at the time of presentation may often be difficult, and cautious evaluation and management of these patients are warranted. The ASRS TSC encourages active postmarketing surveillance by all physicians.